MULTIMORBIDITY INFLUENCES SUPPORT FOR PHYSICAL ACTIVITY AMONG ADULTS WITH OSTEOARTHRITIS AND THEIR PARTNERS. (11th November 2018) - Ellis, K; Cuthberson, C; Rimmler, S; Carthron, D; Phillips, A; Callahan, L; Rini, C
Abstract: Background: Physical activity (PA) reduces pain and disability in people with osteoarthritis (PWOA); however, approximately 47% PWOA are insufficiently active. Multiple health problems ("multimorbidity) is a concerning issue among PWOA and adults overall. Consequently, multimorbidity among PWOA and/or their partners can be a barrier to social support within couples. Yet, the influence of multimorbidity on social support for PA among PWOA remains unknown. Methods: The Partners in Active Living Study (PALS) investigated the role of partner support for PA among insufficiently active PWOA and their partners after a one-time class to encourage partner support. Multivariable adjusted multi-level models were used to estimate how multimorbidity (presence or absence) influenced changes in social support for PA using 5 waves of data from 159 couples over one year. Results: 86% of PWOA and 65% of partners reported multimorbidity. Mean partner support for PA increased over time; partners with multimorbidity reported the lowest mean values. Positive rates of change in support received and provided were observed. PWOA with partners who had multimorbidity reported a greater rate of change in social support received than PWOA without multimorbidity; however, we did not observe a similar pattern when examining partners' own reports of support provided. Conclusions: Partners with multimorbidity reported lower mean social support, but rates of change were greatest among this group. In addition, PWOA with partners who had multimorbidity reported greater changes in support provided than partners' own self-reports. Interventions for PWOA should consider how multimorbidity (presence or absence) influences support for PA within couples.